Arbitration : a very short introduction - Schultz, Thomas (Lawyer); Grant, Thomas (Barrister) (Oxford : Oxford University Press, 2021)
Arbitration is a legal dispute resolution mechanism, alternative to courts. This book explains what arbitration is, how it works, what parties who have agreed to go to arbitration should expect, the relationship between arbitration and the law, and the politics of arbitration. It also considers where the global system of arbitration is headed.
Also issued in print: 2021.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 29, 2021).
Keywords: Arbitration (Administrative law)